Unraveling the Evolutionary Trajectory, and Functional Significance of ALOX5AP: A Proteomic Investigation - Hana Husayin; Esmaiel Saad (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Coronary artery disease (CAD) is a condition that disrupts blood flow to the heart and includes heart attacks, remaining a leading cause of death. The enzyme LTA4H is involved in the inflammatory pathways associated with CAD. ALOX5AP encodes a protein necessary for leukotriene production, which contributes to atherosclerosis progression. Methods. This study aims to analyze ALOX5AP protein diversity, evolution, and selection pressures to understand its biological function. Information was gathered on phylogenetic relationships, and the BLAST tool was used to identify similar proteins and genes. Multiple sequence alignment and phylogenetic tree construction were performed. Results. The highest distribution density of ALOX5AP was observed in Homo sapiens, followed by isoforms of other organisms. Evaluation of selection pressures indicated purifying selection in most codons, with a few showing neutral or positive selection. Conclusion. The study found that Tupaia chinensis is likely the earliest known form of ALOX5AP, while Homo sapiens represents the most recent sequences, suggesting a rapid evolution in primates and other higher organisms, and that positive selection of ALOX5AP isoforms in Homo sapiens may contribute to the higher prevalence of ALOX5AP proteins in human CAD.